Kompetensi Informatika Perawat dan Kualitas Dokumentasi Asuhan Keperawatan - Gusrina Komara Putri; Moh. Heri Kurniawan (FORIKES, 2021)
The development of nursing service technology makes nursing informatics applications develop rapidly. This study aims to analyze the relationship between the informatics competence of nurses and the quality of nursing care documentation. The study design was cross-sectional, involving 220 nurses in the hospital. Data were collected through filling out the Self-Assessment of Nursing Informatics Competencies (SANIC) questionnaire and modification of the Quality of Diagnosis, Intervention and Outcomes (QDIO). The collected data were analyzed using the Partial Least Square (PLS) test. The results of this study indicated a correlation between age, years of service and clinical level with the informatics competence of nurses. Keywords: nursing informatics; nursing documentation; nurse ABSTRAK Perkembangan teknologi pelayanan keperawatan membuat aplikasi informatika keperawatan berkembang dengan pesat. Penelitian ini bertujuan untuk menganalisis hubungan antara kompetensi informatika perawat dengan kualitas dokumentasi asuhan keperawatan. Desain penelitian ini adalah cross-sectional, yang melibatkan 220 perawat di rumah sakit. Data dikumpulkan melalui pengisian kuisioner Self-Assessment of Nursing Informatics Competencies (SANIC) dan modifikasi dari Quality of Diagnosis, Intervention and Outcomes (QDIO). Data yang telah terkumpul dianalisis menggunakan uji Partial Least Square (PLS). Hasil dari penelitian ini menunjukkan adanya korelasi antara umur, masa kerja dan jenjang klinik dengan kompetensi informatika perawat. Kata kunci: informatika keperawatan; dokumentasi keperawatan; perawat